Renee: End-to-end training of extreme classification models - Jain, Vidit; Prakash, Jatin; Saini, Deepak; Jiao, Jian; Ramjee, Ramachandran; Varma, Manik (In Proceedings of the Conference on Machine Learning and Systems, Miami, Florida, 2023)
The goal of Extreme Multi-label Classification (XC) is to learn representations that enable mapping input texts to the most relevant subset of labels selected from an extremely large label set, potentially in hundreds of millions. Given the extreme scale, conventional wisdom believes it is infeasible to train an XC model in an end-to-end manner. Thus, for training efficiency, several modular and sampling-based approaches to XC training have been proposed in the literature. In this paper, we identify challenges in the end-to-end training of XC models and devise novel optimizations that improve training speed over an order of magnitude, making end-to-end XC model training practical. Furthermore, we show that our end-to-end trained model, Renee´ delivers state-of-the-art accuracy in a wide variety of XC benchmark datasets. Code for Renee is available at https://github.com/microsoft/renee.